American Geriatrics Society/Association of Directors of Geriatric Academic Programs Curricular Milestones for Graduating Geriatric Fellows1. Issue 5 (18th April 2014) - Parks, Susan M.; Harper, G. Michael; Fernandez, Helen; Sauvigne, Karen; Leipzig, Rosanne M.
<x xml:space="preserve">Abstract</x> This article describes the curricular milestones for geriatric fellows and the process used to develop them. The curricular milestones were developed to determine what every graduating geriatric fellow should be able to demonstrate to ensure that they will be able to practice effectively and safely in all care settings and with different older adult populations. Three major domains were identified: Caring for the Elderly Patient, Systems‐Based Care for Elder Patients, and Geriatric Syndromes. Six hundred thirty‐five geriatricians each reviewed and commented on one domain. These geriatricians represented important stakeholder groups: geriatric fellowship program directors; Association of Directors of Geriatric Academic Programs (ADGAP) members, who are primarily geriatric program and fellowship directors; the American Geriatrics Society (AGS) and ADGAP Education Committee; the AGS Teacher's Section; Geriatric Academic Career Award awardees; and through the American Board of Internal Medicine and the American Board of Family Medicine, board‐certified geriatricians who spend more than 50% of their time in clinical practice. The AGS and ADGAP boards approved the final set of 76 Geriatric Curricular Milestones, which were posted on the Portal of Geriatric Online Education in December 2012. These curricular milestones are intended to assist geriatric fellowship directors as they develop curricula and assessments to inform program director reporting to the Accreditation Council for Graduate Medical Education in the Next Accreditation System, which begins in July 2014.